Ghost blows a kiss - Hart, Carolyn G. (Hart, Carolyn G. Bailey Ruth ghost mysteries, 2021)
"The late - as in Dearly Departed - Bailey Ruth Raeburn is delighted when she's assigned a new mission by Heaven's Department of Good Intentions, even if she is no good at following the rules for Earthly Visitations. This time she's determined to be the perfect unseen emissary, no matter what it takes. Arriving late in the evening in her old hometown of Adelaide, Oklahoma to find a woman drowning in a pond, Bailey Ruth carries out a daring rescue with textbook invisible effort. But Bailey Ruth soon realizes there's more to Fran's accident than a late-night walk gone wrong. The young widow was running away - but what from? Soon Bailey Ruth finds herself caught up in a complex web of family secrets, loyalties and lies - and if she doesn't act fast, an innocent will be locked up for a very long time."--Publisher.